Mendorong Keunggulan Bersaing melalui Integrasi Strategi Bisnis Hijau dan Pemasaran Berkelanjutan: Studi pada UMKM Fesyen di Kabupaten Banyumas - Puspita Lianti Putri; Iin Dyah Indrawati (Sekolah Tinggi Ilmu Ekonomi Pariwisata Indonesia Semarang, 2025)
The increasing international awareness of environmental issues has had a significant impact on business orientation in various sectors, including micro, small, and medium enterprises (MSMEs). In the fashion industry, MSMEs are not only required to create innovations in product design and quality, but are also directed to adopt environmentally friendly practices that support sustainability throughout their business processes, from production to marketing. This study aims to examine in depth how the integration of green business strategies and sustainable marketing contributes to increasing the competitive advantage of fashion MSMEs in Banyumas Regency, Indonesia. This study uses a quantitative approach with a survey method involving 100 fashion MSME respondents selected based on relevant criteria. Data processing was carried out through multiple linear regression analysis accompanied by classical assumption tests with the help of SPSS software, so that the research results have a strong empirical basis. The research findings indicate a positive and significant influence, both partially and simultaneously, between the implementation of green business strategies and sustainable marketing on achieving competitive advantage. The coefficient of determination (R²) value of 0.52 indicates that the two independent variables are able to explain more than half of the variation in competitive advantage possessed by MSMEs. The implications of these results confirm that the success of MSMEs no longer depends solely on product innovation, but also on the ability to integrate sustainability aspects into internal practices and external strategies. This research enriches the literature on sustainable management, particularly in the context of MSMEs in non-urban areas, while also providing practical input for the formulation of business assistance policies that are adaptive to market dynamics and increasingly complex environmental challenges. This research provides theoretical contributions to the literature on sustainable management in the context of MSMEs in non-urban areas, as well as practical implications for the development of business assistance policies that are more adaptive to environmental challenges.